Additive manufacture of three dimensional nanocomposite based objects through multiphoton fabrication - Liu, Yaan; Hu, Qin; Zhang, Fan; Tuck, Christopher; Irvine, Derek; Hague, Richard J.M.; Yinfeng, He; Simonelli, Marco; Rance, Graham; Smith, Emily; Wildman, Ricky D. (MDPI, 2016)
Three dimensional structures prepared from a gold-polymer composite formulation have been fabricated using multiphoton lithography. In this process, gold nanoparticles were simultaneously formed through photoreduction whilst polymerisation of two possible monomers was promoted. The monomers, trimethylopropane triacrylate (TMPTA) and pentaerythritol triacrylate (PETA) were mixed with a gold salt, but it was found that the addition of a Ruthenium (II) complex enhanced both the geometrical uniformity and integrity of the polymerized / reduced material, enabling the first production of 3D gold-polymer structures by single step multiphoton lithography.